Balanced Scorecard and Strategic Alignment: A Malaysian Case - Ayoup, Hazeline; Omar, Normah; Rahman, Ibrahim Kamal Abdul (International Journal of Economics and Financial Issues, 2016)
This study explores the uses of the Balanced Scorecard (BSC) as a strategic alignment tool in a large Malaysian organization. The aim is to investigate whether the BSC helps to improve the strategic alignment process in an organization. The authors apply qualitative case study approach. The main sources of data were from interviews and observations. The case company for this study is a large Malaysian Government-Link Company (GLC). The results show that the BSC through its measures helps to improve the process of aligning the company’s strategic objectives and strategies between the top and the lower management levels partially. It reveals how the BSC helps to improve the alignment process by increasing managers’ awareness and common understanding of alignment, focus managers’ attention on the harmonization and streamlining managers’ objectives towards achieving organizational goals. Keywords: Business Management, Performance Management, Balanced Scorecard, Strategic Alignment, Case Study. JEL Classifications: M1, M10, M12, M19